2018
DOI: 10.1093/mnras/sty2862
|View full text |Cite
|
Sign up to set email alerts
|

Performance test of QU-fitting in cosmic magnetism study

Abstract: QU-fitting is a standard model-fitting method to reconstruct distribution of magnetic fields and polarized intensity along a line of sight (LOS) from an observed polarization spectrum. In this paper, we examine the performance of QU-fitting by simulating observations of two polarized sources located along the same LOS, varying the widths of the sources and the gap between them in Faraday depth space, systematically. Markov Chain Monte Carlo (MCMC) approach is used to obtain the best-fit parameters for a fittin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Anderson et al 2015). To our knowledge, there is currently no literature examining the accuracy of QU-fitting when applied to complexity classification specifically, though Miyashita et al (2019) analyse its effectiveness on identifying the structure of twocomponent sources. Brown (2011) suggested Faraday moments as a method to identify complexity, a method later used by Farnes et al (2014) and Anderson et al (2015), but again no literature examines the accuracy.…”
Section: Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson et al 2015). To our knowledge, there is currently no literature examining the accuracy of QU-fitting when applied to complexity classification specifically, though Miyashita et al (2019) analyse its effectiveness on identifying the structure of twocomponent sources. Brown (2011) suggested Faraday moments as a method to identify complexity, a method later used by Farnes et al (2014) and Anderson et al (2015), but again no literature examines the accuracy.…”
Section: Prior Workmentioning
confidence: 99%
“…Being able to identify which sources are simple lets us produce a reliable rotation measure grid from background sources, and being able to identify which sources might be complex allows us to find sources to follow-up with slower polarisation analysis methods that may require manual oversight, such as QU-fitting (as seen in, e.g. Miyashita et al 2019;O'Sullivan et al 2017). In this paper, we introduce five simple, interpretable features representing polarised spectra, use these features to train machine learning classifiers to identify Faraday complexity, and demonstrate their effectiveness on real and simulated data.…”
Section: Introductionmentioning
confidence: 99%
“…RMCLEAN is a CLEAN algorithm (Heald, Braun, & Edmonds 2009) that is typically used to deconvolve the RM synthesis signal. Recent studies that use these methods to study the complexity of a Faraday rotated signal include Farnsworth et al (2011), O'Sullivan et al (2012, Ideguchi et al (2014), Kumazaki et al (2014), Sun et al (2015), Pasetto et al (2018), Miyashita et al (2018), Thomson et al (2021). Each method is limited by the range and number of observed wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Ndiritu et al (2021) suggested the use of Gaussian process modeling to interpolate gaps in the polarization spectrum to improve the FDF reconstruction. Meanwhile, a popular technique is QU -fitting (Farnsworth et al 2011;O'Sullivan et al 2012;Ozawa et al 2015;Kaczmarek et al 2017;Sakemi et al 2018;Schnitzeler & Lee 2018;Miyashita et al 2019), which assumes that the FDF can be approximated by a single or a combination of simple analytic functions such as Gaussian, top-hat, or delta functions. RM CLEAN (e.g., Heald et al 2009;Anderson et al 2016;Michilli et al 2018) is a matching pursuit algorithm that assumes the FDF to be a collection of pointlike sources.…”
Section: Introductionmentioning
confidence: 99%

Wavelets and sparsity for Faraday tomography

Cooray,
Takeuchi,
Ideguchi
et al. 2021
Preprint
Self Cite